Stimulation and Enhancement of Near‐Band‐Edge Emission in Zinc Oxide by Distributed Bragg Reflectors. Issue 10 (7th February 2022) - Kothe, Linda; Albert, Maximilian; Meier, Cedrik; Wagner, Thorsten; Tiemann, Michael
Abstract: The free exciton transition (near‐band‐edge emission, NBE) of ZnO at ≈388 nm can be strongly enhanced and even stimulated by an underlying photonic structure. 1D Photonic crystals, so‐called distributed Bragg reflectors, are utilized to suppress the deep‐level emission of ZnO (DLE, ≈500–530 nm). The reflector stacks are fabricated in a layer‐by‐layer procedure by wet‐chemical synthesis. They consist of low‐ε porous SiO2 layers and high‐ε TiO2 layers. Varying the thickness of the SiO2 layers allows tuning the optical bandgap in a wide range between ≈420 and 800 nm. A ZnO layer is deposited on top of the reflector stacks by sol–gel synthesis. The spontaneous photoluminescence (PL) emission of the ZnO film is modulated by the photonic structure. When the optical bandgap of the reflector is in resonance with the deep‐level emission of ZnO (DLE, ≈500–530 nm), then this defect‐related emission mode is suppressed. Strong NBE emission is observed even when the ZnO layer does not show any NBE emission (due to low crystallinity) in the absence of the photonic structure. With this cost‐efficient synthesis method, emitters for, e.g., luminescent gas sensors can be fabricated. Abstract : One‐dimensional photonic crystals, so‐called distributed Bragg reflectors, are used to modulate the photoluminescence (PL) properties of ZnO. Designing an appropriate optical bandgap in the photonic structure can suppress unwanted, defect‐related deep‐level emission, while the free exciton transition (near‐band‐edge emission, NBE) is strongly enhanced.